Electrostatic interactions play an essential role in the binding of oleic acid with α‐lactalbumin in the HAMLET‐like complex: A study using charge‐specific chemical modifications. Issue 1 (29th September 2012) - Xie, Yongjing; Min, Soyoung; Harte, Níal P.; Kirk, Hannah; O'Brien, John E.; Voorheis, H. Paul; Svanborg, Catharina; Hun Mok, K.
Abstract Human α‐lactalbumin made lethal to tumor cells (HAMLET) and its analogs are partially unfolded protein‐oleic acid (OA) complexes that exhibit selective tumoricidal activity normally absent in the native protein itself. To understand the nature of the interaction between protein and OA moieties, charge‐specific chemical modifications of lysine side chains involving citraconylation, acetylation, and guanidination were employed and the biophysical and biological properties were probed. Upon converting the original positively‐charged lysine residues to negatively‐charged citraconyl or neutral acetyl groups, the binding of OA to protein was eliminated, as were any cytotoxic activities towards osteosarcoma cells. Retention of the positive charges by converting lysine residues to homoarginine groups (guanidination); however, yielded unchanged binding of OA to protein and identical tumoricidal activity to that displayed by the wild‐type α‐lactalbumin‐oleic acid complex. With the addition of OA, the wild‐type and guanidinated α‐lactalbumin proteins underwent substantial conformational changes, such as partial unfolding, loss of tertiary structure, but retention of secondary structure. In contrast, no significant conformational changes were observed in the citraconylated and acetylated α‐lactalbumins, most likely because of the absence of OA binding. These results suggest that electrostatic interactions between the positively‐charged basic groups on α‐lactalbumin and the negatively‐charged carboxylate groups on OA molecules play an essential role in the binding of OA to α‐lactalbumin and that these interactions appear to be as important as hydrophobic interactions. Proteins 2013. © 2012 Wiley Periodicals, Inc.